This empirical study examines intensive interview data collected from eight (N=8) former members of white supremacist organizations in order to understand the meanings of exit – that is, disengagement and deradicalization – from the extremist’s perspective. Using a thematic analysis approach, our findings build on the distinction in the existing exit literature between push and pull factors and the process of role exit identified by Ebaugh (1988). These push and pull factors as well as social identity, we argue, are subsumed within a complex exit process, which includes disengagement, identity deconstruction, and transgressive and transitional relationships. For some, this process culminated in an accomplished identity reconstruction and deradicalization. Most importantly, our findings suggest that exit is linked to entry by a developmental drive that we call the participant’s core need. The core need was the background motivator of entry, disengagement, exit, and ultimately deradicalization. We think that this identity reconfiguration and core needs framework may help make heterogenous exit trajectories that have remained puzzling for researchers more understandable. - Anna Warrington; Frederik Carl Windfeld (Journal for Deradicalization, 2020)
Is there a visual discursive space for the radical(ized) woman or is she invisible? The following paper develops an analytical framework to further the understanding of the interplay between gender and security in radicalization studies. Drawing on visuality research and feminism in security studies, this paper provides a new perspective on the visual representation of female agency. The agency of the violent extremist woman is, for the most part, visually (re)constructed through or with a masculine gaze - as defiance, allure and/or coercion. We argue that the connotations of images are shaped within and by an intervisual and intertextual dynamic that (re)produces understandings of female violence as pathologized, victimized and/or sensationalized and contingent on/in relation to male politics. Using this framework, we analyze the interplay between a textual and visual representation of Hasna Ait Boulahcen labeled ‘The first Europan female suicide bomber’ in Danish media following a violent incident in Paris in 2015. Our analysis illustrates how gendered markers of identity continuously reproduce what is possible in securitized discursive realms insofar that a process of Othering Hasna is gendered. This gendered discursive approach contributes to the understanding of deradicalization by underscoring the role of Silencing and Othering of violent extremist women in shaping and narrowing the discursive realm of political opportunities. The paper thus highlights the role of media representations in limiting the discursive possibilities within and therefore efficacy of deradicalization research, policy and programs.